2014
DOI: 10.1016/j.medici.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microsatellite instability on survival of endometrial cancer patients

Abstract: Our study showed no statistically significant relationship between MSI-high and survival of endometrial cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
3
14
2
2
Order By: Relevance
“…On the other hand, there was no significant difference in survival of these patients and they suggested that immune surveillance associated with MMR defects may counteract the effects of negative prognostic factors in these patients (Mc Meekin et al, 2016). Similarly in another study MSI-high status was detected in 15.6% endometrial cancers while no statistically significant differences between patients with MSI-high and MSI stable tumors was found after stage, histology and tumor grade adjustment on multivariate analysis (Kanopiene et al, 2014). Our results are concordant with these findings as we found association of MSI+ endometrial cancers with high TNM/ FIGO stage, however there was no association found with disease free survival.…”
Section: Cervical Invasionsupporting
confidence: 90%
“…On the other hand, there was no significant difference in survival of these patients and they suggested that immune surveillance associated with MMR defects may counteract the effects of negative prognostic factors in these patients (Mc Meekin et al, 2016). Similarly in another study MSI-high status was detected in 15.6% endometrial cancers while no statistically significant differences between patients with MSI-high and MSI stable tumors was found after stage, histology and tumor grade adjustment on multivariate analysis (Kanopiene et al, 2014). Our results are concordant with these findings as we found association of MSI+ endometrial cancers with high TNM/ FIGO stage, however there was no association found with disease free survival.…”
Section: Cervical Invasionsupporting
confidence: 90%
“…Conversely, Mackay et al found that MSI tumors were common in patients with early‐stage disease, but were associated with worse prognosis in this cohort. Kanopiene et al evaluated 109 cases of endometrial cancer for MSI and found that there was no significant difference in survival rate between MSI and MSS tumors . An et al and Bilbao et al found that, in both early FIGO stage (I and II) and late FIGO stage III and IV endometrial cancer, MSI status was associated with higher grade, deeper myometrial invasion, and higher clinical stage with presence of lymph node metastases; however, we did not observe these correlations in our study probably because of the small sample size and since we did not have any patients with stage IV disease.…”
Section: Discussioncontrasting
confidence: 76%
“…24,25 However, a later study, in 2014, showed no associations of MSI status with survival, tumor grade, tumor stage, or histologic examination findings in 109 patients. 26 In our study, a correlation between International Federation of Gynecology and Obstetrics grade and MSI status was observed. However, MSI status did not correlate with age at diagnosis or other pathologic characteristics, such as American Joint Committee on Cancer stage, tumor site, histologic type, cervix involvement, lymph-vascular invasion, tumor margin, or myometrial invasion, potentially due to our limited study cohort.…”
Section: Discussionsupporting
confidence: 63%